2012
DOI: 10.5402/2012/723157
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Knowledge of Sterculia setigera Del. in the Sudanian Zone of Togo (West Africa)

Abstract: Ethnobotanical knowledge is useful in development of management and conservation of plant genetic resources. In this study, ethnobotanical investigations were conducted in Sudanian zone of Togo to identify use values knowledge of Sterculia setigera tree. Information was obtained with the aid of semistructured interviews. Three (3) ethnic groups: Bassar, Moba, and Konkomba belonging to ten (10) localities were investigated. Use knowledge of Sterculia setigera through these ethnic groups was assessed using four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 14 publications
(17 reference statements)
7
24
0
4
Order By: Relevance
“…The use values of S. setigera plant parts were assessed by comparing the mean reported use values between ethnic groups, gender, age, and occupation. The knowledge of local use of S. setigera was assessed using four use indices (Atakpama et al 2012, Avocevou-Ayisso et al 2012: the reported use (RU), the plant part value (PPV), the specific reported use (SU), and the intraspecific use value (IUV).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use values of S. setigera plant parts were assessed by comparing the mean reported use values between ethnic groups, gender, age, and occupation. The knowledge of local use of S. setigera was assessed using four use indices (Atakpama et al 2012, Avocevou-Ayisso et al 2012: the reported use (RU), the plant part value (PPV), the specific reported use (SU), and the intraspecific use value (IUV).…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge varies according to locality, gender, ethnicity, cultural belief, and interrelation such as intercultural marriages, friendships, and religions (Atakpama et al 2012, Atato et al 2010, Avocevou-Ayisso et al 2012, Ayantunde et al 2008. It could be also influenced by age, occupation (Ayantunde et al 2007, Poderoso et al 2012, Schunko et al 2012, environmental factors such as re- …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations